The Impact of Galaxy Formation on the Diffuse Background Radiation - Silk, J; Devriendt, J (2000)
The far infrared background is a sink for the hidden aspects of galaxy formation. At optical wavelengths, ellipticals and spheroids are old, even at $z \sim 1.$ Neither the luminous formation phase nor their early evolution is seen in the visible. We infer that ellipticals and, more generally, most spheroids must have formed in dust-shrouded starbursts. In this article, we show how separate tracking of disk and spheroid star formation enables us to infer that disks dominate near the peak in the cosmic star formation rate at $z \lapproxeq 2$ and in the diffuse ultraviolet/optical/infrared background, whereas spheroid formation dominates the submillimetre background.